Prevention of Violations by Members of the Criminal Investigation Unit by Division of Profession and Security of Indonesian National Police in the Context of Realizing Precision Police with Scenario Based Strategic Planning - Cita Karunia Sari; Retno Kusumastuti (Department of Public Administration, 2023)
In conditions full of uncertainty, the organization must have the right efforts and strategies to defend itself, by keeping up with the times that are always happening. Indonesian National Police (Polri) as one of the organizations that has an important role in carrying out an orderly and orderly life. The Polri must be able to follow and adapt to technological developments and of course prepare strategies to deal with all uncertainties that continue to occur, especially in the field of security and public order, as well as services to Public. The challenges and tasks for the Polri are becoming increasingly difficult because the community is increasingly critical, and capable and always abreast of developments in every activity carried out by the Polri. In the last few months there have been several cases that have gone viral on social media, especially cases related to law violations committed by members of the Indonesian National Police. These cases which were caused by mistakes made by the Polri members became interesting material and were continuously discussed by the public. This is a big challenge for the Polri, especially the Professional and Security Division of the Indonesian National Police, in order to reduce and prevent violations committed by members of the Polri, with the aim of creating a precise Polri. The results of this study suggest that the method that can be used by the Professional and Security Division of the Indonesian National Police is to use Scenario Based Strategic Planning. In addition to using the SBSP, the process of recruiting Polri members must also be an important concern, so that the newly admitted members have good skills and morality so that opportunities to commit violations of the law are minimized.